Source of Enhancing Mothers Role in The Light of Hadiths Sahih al-Bukhari - Norzulaili Mohd Ghazali; Mesbahul Hoque; Mawaddah Abd Manan; Robiatul Adawiyah Mohd (Islam Transformatif : Journal of Islamic Studies, 2023)
Abstract Islamic interpretation stabilize the mothers as one of the primary individuals directly responsible for managing their children's lives. However, studies have indicated a concerning decline in the institution of the family, which significantly impacts children's well-being. Furthermore, the demands of contemporary careers often lead to the neglect of mothers' parental responsibilities towards their children. Addressing this crucial issue calls for empowering the role of mothers, this study aims to explore the aspects that require attention and improvement from mothers as they fulfill their roles based on the Hadiths of Sahih al-Bukhari. Employing a qualitative research design, the study utilizes inductive thematic analysis to extract valuable insights from the Hadiths. After extracting the hadiths of the mothers' role from Sahih al-Bukhari using words closely related to the word "umm", this study analyses the hadiths from the books of explanation of hadith. Based on the understanding from the analysis, the theme of the mothers' role was formed. Thefindings have identified six essential aspects concerning the role of mothers, encompassing spiritual, physical, emotional, moral, social, and sexual dimensions. By focusing on these six areas, mothers can effectively cultivate a comprehensive and balanced identity for their children, addressing both worldly and spiritual aspects. Keyword: Mother's role, empowerment of mother's role, formation of child's identity, Hadith. Sumber Islam telah menerangkan bahawa ibu salah seorang insan yang bertanggungjawab mengurus kehidupan anak-anak. Meskipun begitu, disebabkan kesibukan ibu masa kini dalam urusan kerjaya telah menyebabkan peranan mereka terhadap anak terabai. Di samping kekurangan komunikasi dan perhatian daripada ibu turut mengakibatkan anak terlibat dalam masalah sosial. Berdasarkan masalah yang disebutkan, satu perbincangan mengenai pemerkasaan peranan ibu perlu dilakukan. Justeru, kajian yang dilakukan ini akan meneliti aspek yang perlu diberi perhatian dan ditingkatkan oleh ibu dalam menjalankan peranannya sebagai ibu menurut hadis sahih al-Bukhari. Dalam mencapai objektif kajian, kajian ini menggunakan reka bentuk kualitatif dan dianalisis secara tematik induktif. Setelah mengekstrak hadis daripada kitab sahih al-Bukhari menggunakan perkataan yang berkait rapat demgan perkataan umm (ibu), seterusnya kajian ini menganalisis hadis-hadis tersebut daripada kitab-kitab penerangan hadis. Berdasarkan pemahaman daripada analisis tersebut, tema peranan ibu terhadap anak dibentuk.  Hasil kajian mendapati sebanyak enam aspek yang diketengahkan dalam hadis-hadis berkaitan peranan ibu. Aspek-aspek yang perlu diperhatikan oleh ibu dalam mengurus anaknya ialah spiritual, jasmani, emosional akhlak, sosial dan seksual. Keenam aspek ini dapat membantu ibu dalam membentuk jati diri yang utuh dan seimbang antara dunia dan akhirat. Kata Kunci: Peranan ibu, Pemerkasaan Peranan Ibu, Pembentukan Diri Anak, Hadis